Comparison of CYB Gene Sequence for Species Identification of Tuna Fish - Beivy Jonathan Kolondam (Jurnal Ilmiah PLATAX, 2020)
DNA barcoding is a reliable tool for species identification, especially for authentication of processed fish products. In the process of authentication of tuna fish products, this tool is needed due to its small sample requirement for species identification. This research aimed to conduct an assessment for the use of the Cytochrome B (CYB) gene sequence for tuna fish identification through DNA barcoding. The same set of mitochondrial DNA genomes were used for the previous COI gene for in silico comparison of tuna fish species. Group comparison of the CYB gene between Bluefin tuna (five species), Yellowfin tuna (three species), and other groups of tuna (five species) showed that this gene is reliable to differentiate all of the specimens of each species. The result displayed by the multiple sequence alignment indicated enough resolution for accurate identification. The problem in the differentiation of Thunnus orientalis dan T. thynnus by the COI gene in the previous study was finally resolved by the CYB gene. From 1141 bp of nucleotides compared in all specimens, there were 248 differentiation sites. All of the members of Thunnus were differentiated for other genera (Auxis, Euthynnus, and Katsuwonus) in 40 differentiation sites.Â Keywords: DNA barcoding; CYB gene; tuna fishAbstrakDNA barcoding merupakan perangkat yang dapat diandalkan untuk identifikasi spesies ikan, terutama untuk kepentingan autentifikasi produk-produk olahan hasil perikanan. Dalam proses autentifikasi produk hasil olahan ikan tuna memerlukan metode ini karena hanya membutuhkan sampel yang sangat sedikit untuk identifikasi spesies. Penelitian ini bertujuan untuk melakukan asesmen terhadap penggunaan sekuens gen sitokrom B (CYB) untuk identifikasi ikan tuna lewat DNA barcoding. Genom DNA mitokondria yang sama dengan penelitian gen COI sebelumnya digunakan untuk perbandingan secara in silico spesies-spesies ikan tuna. Perbandingan sekuens gen CYB pada kelompok ikan tuna Bluefin (lima spesies), kelompok ikan tuna Yellowfin (tiga spesies), dan kelompok ikan tuna jenis lain (lima spesies) menunjukkan bahwa gen ini mampu membedakan semua spesies yang dibandingkan. Hasil yang digambarkan dari penjajaran sekuens menunjukkan resolusi yang cukup untuk identifikasi secara akurat. Spesies Thunnus orientalis dan T. thynnus yang memiliki variasi sekuens yang identik di gen COI berdasarkan penelitian sebelumnya ternyata bisa dibedakan melalui gen CYB ini. Dari 1.141 bp nukleotida yang dibandingkan, terdapat 248 titik perbedaan. Semua anggota dari genus Thunnus berbeda dengan spesimen dari genus-henus lainnya (Auxis, Euthynnus, dan Katsuwonus) di 40 titik nukleotida.Kata kunci: DNA barcoding; gen CYB; ikan tuna